A Novel Recurrent COL5A1 Genetic Variant Is Associated With a Dysplasia-Associated Arterial Disease Exhibiting Dissections and Fibromuscular Dysplasia. Issue 11 (November 2020) - Richer, Julie; Hill, Hannah L.; Wang, Yu; Yang, Min-Lee; Hunker, Kristina L.; Lane, Jamie; Blackburn, Susan; Coleman, Dawn M.; Eliason, Jonathan; Sillon, Guillaume; D'Agostino, Maria-Daniela; Jetty, Prasad; et al.
Abstract : Objective: While rare variants in the COL5A1 gene have been associated with classical Ehlers-Danlos syndrome and rarely with arterial dissections, recurrent variants in COL5A1 underlying a systemic arteriopathy have not been described. Monogenic forms of multifocal fibromuscular dysplasia (mFMD) have not been previously defined. Approach and Results: We studied 4 independent probands with the COL5A1 pathogenic variant c.1540G>A, p.(Gly514Ser) who presented with arterial aneurysms, dissections, tortuosity, and mFMD affecting multiple arteries. Arterial medial fibroplasia and smooth muscle cell disorganization were confirmed histologically. The COL5A1 c.1540G>A variant is predicted to be pathogenic in silico and absent in gnomAD. The c.1540G>A variant is on a shared 160.1 kb haplotype with 0.4% frequency in Europeans. Furthermore, exome sequencing data from a cohort of 264 individuals with mFMD were examined for COL5A1 variants. In this mFMD cohort, COL5A1 c.1540G>A and 6 additional relatively rare COL5A1 variants predicted to be deleterious in silico were identified and were associated with arterial dissections ( P =0.005). Conclusions: COL5A1 c.1540G>A is the first recurring variant recognized to be associated with arterial dissections and mFMD. This variant presents with a phenotype reminiscent of vascular Ehlers-Danlos syndrome. A shared haplotype among probands supports the existence of a common founder. Relatively rare COL5A1 genetic variants predicted to be deleterious by in silico analysis were identified in ≈2.7% of mFMD cases, and as they were enriched in patients with arterial dissections, may act as disease modifiers. Molecular testing for COL5A1 should be considered in patients with a phenotype overlapping with vascular Ehlers-Danlos syndrome and mFMD. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.